2008
DOI: 10.1111/j.1834-7819.2007.00005.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dental care on oral health‐related quality of life and treatment goals among elderly adults

Abstract: Background:  General dental care can effectively control disease and restore damaged tissue, yet little is known about its impact on patients’ subjective oral health, namely treatment goals and oral health‐related quality of life (OHRQoL). This study aimed to evaluate change in both aspects of subjective oral health among elderly adults receiving publicly‐funded, general dental care.Methods:  We conducted a prospective, single‐group intervention study of adults aged 75+ years receiving care through the South A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 19 publications
5
29
0
1
Order By: Relevance
“…Notably, only 27% of employees at baseline had visited a dentist within the last year, less than half the Australian national estimate of 59.3% (Spencer & Harford, 2007) and closer to estimates for other disadvantaged populations such as the homeless (Ford, Cramb, & Farah, 2014). The benefits suggested by dental treatment in this study further underline the importance of routine dental care for the subpopulation of people with special needs, as has been demonstrated in several studies for the general population (Crocombe, Brennan, & Slade, 2011) and older adults (Gagliardi, Slade, & Sanders, 2008;Locker, 2001).…”
Section: Discussionsupporting
confidence: 80%
“…Notably, only 27% of employees at baseline had visited a dentist within the last year, less than half the Australian national estimate of 59.3% (Spencer & Harford, 2007) and closer to estimates for other disadvantaged populations such as the homeless (Ford, Cramb, & Farah, 2014). The benefits suggested by dental treatment in this study further underline the importance of routine dental care for the subpopulation of people with special needs, as has been demonstrated in several studies for the general population (Crocombe, Brennan, & Slade, 2011) and older adults (Gagliardi, Slade, & Sanders, 2008;Locker, 2001).…”
Section: Discussionsupporting
confidence: 80%
“…Considering dental problems, more than three fifth of studied sample had loss of teeth as a dental problem (Figure1). This result was similar to [26].who studied"Impact of dental care on oral health-related quality of life and treatment goals among elderly adults". They revealed that the more percent's of studied sample had tooth loss.…”
Section: Discussionsupporting
confidence: 76%
“…By way of comparison, a clinical study of general dental treatment among older dental patients in Australia documented a reduction of 6.2 units of the OHIP score 6 months after completion of treatment 38. In a similar study of Canadians, there was a 4.3 unit reduction in OHIP-14 scores after treatment, and the authors concluded that the minimal important difference for the OHIP-14 was of 5-scale points 39.…”
Section: Discussionmentioning
confidence: 99%